2022
DOI: 10.1002/ijc.33985
|View full text |Cite
|
Sign up to set email alerts
|

Targeting type I collagen for cancer treatment

Abstract: Collagen is the most abundant protein in animals. Interactions between tumor cells and collagen influence every step of tumor development. Type I collagen is the main fibrillar collagen in the extracellular matrix and is frequently upregulated during tumorigenesis. The binding of type I collagen to its receptors on tumor cells promotes tumor cell proliferation, epithelial-mesenchymal transition and metastasis. Type I collagen also regulates the efficacy of tumor therapies, such as chemotherapy, radiotherapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 281 publications
0
21
0
Order By: Relevance
“…The collagen in articular cartilage is chiefly the type II form but other types, including types I and III, have been reported. Type I collagen is abundant in the human body and is the primary constituent of skin, bone, tendon, and blood vessels [ 49 , 50 ]. Mutations in the type I collagen gene cause the Ehlers–Danlos syndrome and osteogenesis imperfecta [ 51 ].…”
Section: Extracellular Matrix In Osteoarthritismentioning
confidence: 99%
“…The collagen in articular cartilage is chiefly the type II form but other types, including types I and III, have been reported. Type I collagen is abundant in the human body and is the primary constituent of skin, bone, tendon, and blood vessels [ 49 , 50 ]. Mutations in the type I collagen gene cause the Ehlers–Danlos syndrome and osteogenesis imperfecta [ 51 ].…”
Section: Extracellular Matrix In Osteoarthritismentioning
confidence: 99%
“…In the progression of PTC, deregulation of focal adhesion kinase (FAK) is observed at both post‐transcriptional and translational levels 39 . Collagen is one of the most abundantly expressed proteins in humans, and collagens are involved at every level of cancer development and establish interactions with cancer cells 40 . One of the recent studies has shown that collagen family genes (especially COL18A1 overexpression) are associated with poor prognosis and can be used as prognostic biomarkers for PTC 41 …”
Section: Discussionmentioning
confidence: 99%
“…Type I collagen is frequently upregulated during tumorigenesis. By binding to its receptors on tumor cells, Type I collagen can promote tumor cell proliferation, epithelial-mesenchymal transition and metastasis, as well as regulate the efficacy of chemotherapy, radiotherapy and immunotherapy [ 63 ]. Therefore, consistent with these reports, our findings suggest that KIAA1199 may be involved in shaping a tumor-friendly TME, thereby accelerating cancer progression and deteriorating prognosis in LUAD patients.…”
Section: Discussionmentioning
confidence: 99%